Stability and explanatory power of inequality aversion: an investigation of the house money effect - Astrid Dannenberg; Thomas Riechmann; Bodo Sturm; Carsten Vogt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
In this paper, we analyse if individual inequality aversion measured with simple experimental games depends on whether the monetary endowment in these games is either a windfall gain ("house money") or a reward for a certain effort-related performance. Moreover, we analyse whether the way of preference elicitation affects the explanatory power of inequality aversion in social dilemma situations. Our results indicate that individual inequality aversion is not generally robust to the way endowments emerge. Furthermore, the use of money earned by real efforts instead of house money does not improve the generally low predictive power of the inequality aversion model. Hypotheses based on the inequality aversion model lose their predictive power when preferences are elicited with earned money.
Keywords: C91; C92; H41; 330; individual preferences; inequality aversion; experimental economics; prisoner's dilemma; house money; Soziale Ungleichheit; Gerechtigkeit; Präferenztheorie; Test; Gefangenendilemma